2003
DOI: 10.1046/j.1464-410x.2003.04317.x
|View full text |Cite
|
Sign up to set email alerts
|

Previous testicular position in boys referred for an undescended testis: further explanation of the late orchidopexy enigma?

Abstract: RESULTSOn referral, 340 testes were not in the scrotum (182 uni-and 79 bilateral). Of the 340 testes, 82 (24%) in 61 boys were diagnosed as retractile, whereas the remaining 258 in 221 boys were undescended. The previous testicular position was known in 208 of 221 boys (94%), with 244 UDTs. In 65 of these 244 (26.6%) the testis had never been scrotal (congenital UDT); in 179 (73.4%) a previous intrascrotal position was recorded in early childhood (acquired UDT) at least once, in 149 (61%) at least twice and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 31 publications
5
61
0
2
Order By: Relevance
“…The elevated risk of cancer in these testes requires regular exams which are facilitated by orchidopexy which places the testes in the normal anatomic position. In contrast to UDT, secondary testicular ascent of retractile testes has been described as common in some referral populations [2,10,11], and it typically requires only yearly exams by a primary care provider to ensure proper ultimate position within the scrotum. This secondary process may lead to a bimodal referral pattern of patients with undescended testes, infants and those greater than 2 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated risk of cancer in these testes requires regular exams which are facilitated by orchidopexy which places the testes in the normal anatomic position. In contrast to UDT, secondary testicular ascent of retractile testes has been described as common in some referral populations [2,10,11], and it typically requires only yearly exams by a primary care provider to ensure proper ultimate position within the scrotum. This secondary process may lead to a bimodal referral pattern of patients with undescended testes, infants and those greater than 2 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…A UDT was defined as a non-palpable testis inside the scrotum and for which further traction on cord traction was painful (Meij-de Vries A et al 2010). A congenital UDT was defined as a testis which had not previously descended (Meij-de Vries A et al 2010, Hack WW et al 2003b), whereas an acquired UDT was defined as an UDT in which a previous scrotal position was documented on at least one occasion (Barthold JS & González R 2003). This does not include testes identified as being cryptorchid after inguinal surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Clarnette et al (Clarnette et al 1977, Clarnette et al 1997 reported the presence of a fibrous structure extending with the cord structures, which on immunohistochemistry showed the characteristics of a remnant of the PV. Other studies found the presence of PV or hernia sac in 23%-76% of orchiopexies for acquired UDT (Robertson JF & Azmy AF 1988, Wright JE 1989, Meijer RW 2004, Gracia J et al 1997, Eardley I et al 1994, Hack WW 2003b. Based on these findings, it was suggested that the persistence of a patent PV or its remnants is responsible for tethering the testis in a static position during a period of somatic growth.…”
Section: Pathogenesismentioning
confidence: 96%
See 2 more Smart Citations